Simultaneous Detection and Removal of Formaldehyde at Room Temperature: Janus Au@ZnO@ZIF-8 Nanoparticles - Zhang, Dawei; Li, Zhiwei; Zhou, Jian; Fang, Hong; He, Xiang; Jena, Puru; Zeng, Jing-Bin; Wang, Wei-Ning (Nano-Micro Letters, 2017)
The detection and removal of volatile organic compounds (VOCs) are of great importance to reduce the risk of indoor air quality concerns. This study reports the rational synthesis of a dual-functional Janus nanostructure and its feasibility for simultaneous detection and removal of VOCs. The Janus nanostructure was synthesized via an anisotropic growth method, composed of plasmonic nanoparticles, semiconductors, and metal organic frameworks (e.g., Au@ZnO@ZIF-8). It exhibits excellent selective detection to formaldehyde (HCHO, as a representative VOC) at room temperature over a wide range of concentrations (from 0.25 to 100 ppm), even in the presence of water and toluene molecules as interferences. In addition, HCHO was also found to be partially oxidized into non-toxic formic acid simultaneously with detection. The mechanism underlying this technology was unraveled by both experimental measurements and theoretical calculations: ZnO maintains the conductivity, while ZIF-8 improves the selective gas adsorption; the plasmonic effect of Au nanorods enhances the visible-light-driven photocatalysis of ZnO at room temperature. Highlights: 1 Au@ZnO@ZIF-8 Janus nanostructure was designed and synthesized via an anisotropic growth method for the detection of volatile organic compounds (VOCs). 2 Due to the synergistic effects of the high conductivity of ZnO, the superior gas adsorption capability of ZIF-8, the clean interface between ZnO and ZIF-8, and the plasmonic resonance of gold nanorods, the Janus nanostructure demonstrates an excellent sensing performance with a selective detection toward formaldehyde at room temperature.